The Identity Construction of Da'wah Leadership on Jama'ah Tabligh Movement - Dudy Imanuddin Effendy; Dudi Rustandi (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2020)
The presence of religious social groups is driven by the process of leadership emergence. The purpose of this study is to find (1) the concept of leadership of the Tablighi Jamaah from various perspectives; Sufism, jurisprudence, laity, and religious authority; (2) Construction of the identity of the religious leaders of the Jamaah Tabligh. The research paradigm uses virtual ethnographic methods with social identity construction theory. The results showed that (1) the concept of leadership in the Tablighi Jamaah emphasized more on religious authority and charismatic leadership (2) The construction of the religious identity of the leadership dimension of the Tablighi Jama'at was a combination of charismatic and transformational authority. This research can have an impact on the leadership model of social and religious institutions in Indonesia as a model that is quite effective in creating observance of pilgrims.Kehadiran kelompok sosial keagamaan didorong oleh proses munculnya kepemimpinan. Tujuan penelitian ini adalah untuk menemukan (1) konsep kepemimpinan Jamaah Tabligh dari beragam perspektif; sufistik, yurisprudensi, awam, dan otoritas keagamaan; (2) Konstruksi identitas kepemimpinan agama Jamaah Tabligh. Paradigma penelitian menggunakan metode etnografi virtual dengan teori konstruksi identitas social. Hasil penelitian menunjukkan bahwa (1) konsep kepemimpinan pada Jamaah Tabligh lebih menekankan pada otoritas keagamaan dan kepemimpinan yang bersifat kharismatik (2) Konstruksi identitas keagamaan dimensi kepemimpinan Jama’ah Tabligh merupakan perpaduan antara otoritas kharisma dan transformasional. Penelitian ini dapat berdampak terhadap model kepemimpinan instusi social maupun keagamaan di Indonesia sebagai model yang cukup efektif dalam menciptakan ketaatan jamaah.